Life Models in Young People: Ideas of Future Family and Impacts of Parental Models - Moskvicheva N.L; Rean A.A; Kostromina S.N; Grishina N.V; Zinovieva E.V (Moscow State University of Psychology and Education, 2019)
The article substantiates the introduction of the "life model" construct as a fragment of life scenario in a specific area of human life and describes the development of tools for its study. The results of a study on life models of relationships in young people (on a sample of 100 students of St. Petersburg State University, the average age of 21 ± 1.1 years) are presented by the following parameters: the need for creating a family and maintaining close relationships; understanding the nature of relationships in a future family (distribution of responsibility and power); commitment to family life space in comparison with the students' perceptions of their parents' life models. The paper characterises the impact of parental family on the individual's life scenarios. It shows that the consistency of life models reveals itself in the young people's desire to reproduce their parents' model of emotional intimacy in relationships, provided that they evaluate the relationships in their families as successful; no such consistency was found in the professional sphere. Finally, five types of life models in the young people are described, emphasizing the leading role of closeness/distance with parental family in their content, which confirms the fundamental importance of the respondents' orientation towards close relationships with their parental family.